Confession to Make: Inadvertent Confessions and Admissions in United Kingdom and United States Police Contexts - Filipović, Luna (Frontiers in Psychology, 2021)
Previous studies have addressed many different kinds of confessions in police investigations - real, false, coerced, fabricated - and highlighted both psychological and social mechanisms that underlie them (Kassin & Gudjonsson, 2004). Here we focus on inadvertent confessions and admissions, which occur when a suspect appears to be confessing without being fully aware of doing so, or when police officers believe they have a confession or admission of guilt when in fact this is not the case. The goal of the study is to explain when, how and why these confessions and admissions occur as well as how they are dealt with in two different jurisdictions, the US and the UK. We use a discourse analysis approach because inadvertent confessions and admissions of guilt are the product of miscommunication - they happen because the speaker’s meaning and the hearer’s meaning are misaligned (Elder & Haugh, 2018). The data consist of 50 interviews from the UK and 50 interrogations from the United States with both English-speaking and non-English speaking suspects. Our results demonstrate that inadvertent confessions can occur in both locales due to reliance on inference (Grice, 1975), which is inevitable since inference is the backbone of any human communication, as well as due to additional factors such as linguistic, cultural and procedural issues. We found that these phenomena are more frequent and less well controlled for in the US context due to a) no systematic checking of understanding, b) adversarial questioning techniques and an absence of legal representation and c) lack of professional, high-quality interpreting. We discuss the implications of our findings for current efforts to improve access to justice, custodial procedures and language services, and we make recommendations for the implementation of our research in professional practice.